Control of guest binding behavior of metal-containing host molecules by ligand exchange. Issue 13 (23rd March 2021) - Akine, Shigehisa
Abstract : Structural transformation driven by ligand exchange was effectively utilized to control the host–guest binding behavior of metal-containing host molecules. Abstract : This review describes the control of guest binding behavior of metal-containing host molecules that is driven by ligand exchange reactions at the metal centers. Recently, a vast number of metal-containing host molecules including metal-assisted self-assembled structures have been developed, and the structural transformation after construction of the host framework has now been of interest from the viewpoint of functional switching and tuning. Among the various kinds of chemical transformations, ligand exchange has a great advantage in the structural conversions of metal-containing hosts, because ligand exchange usually proceeds under mild conditions that do not affect the host framework. In this review, the structural transformations are classified into three types: (1) weak-link approach, (2) subcomponent substitution, and (3) post-metalation modification, according to the type of coordination motif. The control of their guest binding behavior by the structural transformations is discussed in detail.